Clinical trial capacity building in a pandemic-outcome of a rapid site readiness project in Latin America - Sue Ann Costa Clemens; Sue Ann Costa Clemens; Isabela Gonzalez; Daniele Sereni; Ralf Clemens (Frontiers Media S.A., 2024)
BackgroundLatin America (Latam) has a tradition of large-scale vaccine trials. Because of fluctuating demand, many sites have downsized their infrastructure. Therefore, BMGF launched a clinical trial site-readiness initiative early in the coronavirus-2019 (COVID-19) pandemic including Latam countries between August and September 2020. This survey evaluated clinical development performance measures pre/post initiative (September 2022).Results20/21 prequalified sites participated in COVID-19 vaccine/drug development trials. 156 clinical trials (140 COVID-19 vaccine/drug trials) were initiated in the 2 years since prequalification, compared to 176 in the 5 years before. 33,428/37,810 participants were included in COVID-19 programs. The number of enrolled subjects/day across sites quadrupled from 15 (1-35) to 63 (5-300). The dropout rate was 6.8%. Study approval timelines were reduced from 60 (12-120) to 35 (5-90) days. Mean qualified staff was increased from 24 (6-80) to 88 (22-180).ConclusionClinical trial sites across Latam were successfully prequalified to participate in COVID-19 developments. For the 100 days mission of vaccine availability in a new pandemic sufficient and well-trained clinical trial sites readily available are essential. This is only achievable if sites-especially in low/middle-income countries-are maintained active through a constant flow of vaccine studies.